Firm life cycle, expectation errors and future stock returns - Konstantinidi, Theodosia (Journal of Banking & Finance, 2022)
I study the return predictability of firm life cycle, originally documented by Dickinson (2011). I show that a hedge portfolio strategy going long on mature firms and short on introduction firms generates a significant hedge portfolio return of 1.29% per month in return-weighted portfolios and 0.72% in value-weighted portfolios. The returns to firm life cycle are related to investors’ and analysts’ expectation errors, are driven by market-wide investor sentiment, and are more pronounced among stocks with low institutional ownership and high idiosyncratic volatility. Quantile regressions show that introduction firms have considerably greater uncertainty and skewness in future earnings growth outcomes than mature firms, such that analysts are better able to justify optimistically biased forecasts for introduction firms compared to mature firms.